Analysis of barriers in implementation of blockchain technology in Indian industries. (11th July 2022) - Prasad, Kanika; Kumar, Dinesh; Gupta, Mayank
Blockchain technology could change the way that confidentiality, collaboration and ambiguity are perceived in this digitised world. These features have increased its potential for application in various sectors. However, this technology is still emerging and integrating it with the current system poses several challenges. There are numerous barriers that hinder the successful implementation of blockchain technology in Indian industries. Therefore, in this study a framework based on IF-TOPSIS methodology is developed for analysing various barriers in the implementation of blockchain technology. This work considers 14 such barriers that have been identified through extensive literature review and experts' opinions. Application of the proposed framework showed that 'poor economic behaviour', 'market-based risks' and 'cyber-attack risk' are the most relevant barriers for implementation of the said technology. The study provides an insight to the industries and government to enable proper and successful implementation of the blockchain technology in future industries of India.